Legal Position and Implications of Land Lease Agreements Subject to Mortgage Rights - Himma Hasanah; Amad Sudiro (Jurnal Daulat Hukum, 2026)
This study aims to analyze the legal position of land lease agreements and the legal implications of leasing land encumbered with mortgage rights. The research method used is normative legal research with statutory and conceptual approaches. Legal materials were obtained through library research consisting of primary, secondary, and tertiary legal materials, which were then analyzed qualitatively using a descriptive-analytical method. The novelty of this study lies in the analysis of the relationship between lease rights as personal rights and mortgage rights as material rights, particularly regarding legal protection for tenants when the leased object is executed by creditors. Based on the results of the study, it is concluded that land lease agreements provide tenants with the right to utilize the land; however, their position is weaker than mortgage rights, which possess preferential characteristics and the principle of droit de suite. Consequently, if the debtor defaults and execution is carried out on the collateral object, the tenant may lose the right to use the leased object before the lease period expires. Legal protection for tenants remains limited and largely depends on the contents of the agreement and the creditor’s approval in the Deed of Granting Mortgage Rights, therefore caution is required when entering into land lease agreements in order to minimize potential legal risks.